2022
DOI: 10.1038/s41598-022-18455-7
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis, and in silico studies of quinoline-based-benzo[d]imidazole bearing different acetamide derivatives as potent α-glucosidase inhibitors

Abstract: In this study, 18 novel quinoline-based-benzo[d]imidazole derivatives were synthesized and screened for their α-glucosidase inhibitory potential. All compounds in the series except 9q showed a significant α-glucosidase inhibition with IC50 values in the range of 3.2 ± 0.3–185.0 ± 0.3 µM, as compared to the standard drug acarbose (IC50 = 750.0 ± 5.0 µM). A kinetic study indicated that compound 9d as the most potent derivative against α-glucosidase was a competitive type inhibitor. Furthermore, the molecular doc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…A Lineweaver–Burk plot was generated to identify the type of inhibition and the Michaelis–Menten constant ( K m ) value was determined from the plot between the reciprocal of the substrate concentration (1/[S]) and reciprocal of enzyme rate (1/V) over various inhibitor concentrations. The experimental inhibitor constant ( K i ) value was constructed by secondary plots of the inhibitor concentration [I] versus K m [ 3 , 7 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A Lineweaver–Burk plot was generated to identify the type of inhibition and the Michaelis–Menten constant ( K m ) value was determined from the plot between the reciprocal of the substrate concentration (1/[S]) and reciprocal of enzyme rate (1/V) over various inhibitor concentrations. The experimental inhibitor constant ( K i ) value was constructed by secondary plots of the inhibitor concentration [I] versus K m [ 3 , 7 ].…”
Section: Methodsmentioning
confidence: 99%
“…DM can be classified into three major types: type I DM (insulin-dependent) due to immune-mediated β cells destructions; type II DM (non-insulin-dependent) due to an insulin secretory defect and insulin resistance as well as gestational diabetes that develops during pregnancy [ 2 ]. T2DM accounts for around 90–95% of the diabetic population and has become a major health problem worldwide [ 3 ]. All three types of DM are characterized by chronic high glucose levels which stimulate the generation of ROS that has a pivotal role in diabetic complications [ 4 ] Reducing postprandial hyperglycemia could prevent and minimize the risk of micro-and macro-vascular complications [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibition of the α-glucosidase enzyme can help in delaying the digestion of carbohydrates, thereby reducing the levels of glucose in the blood. As a result, α-glucosidase inhibitors are of great interest as an efficacious and safe therapy for T2DM 7 . Acarbose, miglitol, and voglibose are approved drugs used as α-glucosidase inhibitors to target T2DM; unfortunately, these compounds are associated with deleterious side effects such as abdominal distention, bloating, and diarrhea 8 , 9 .…”
Section: Introductionmentioning
confidence: 99%
“… 16 Researchers have paid great attention to synthesizing small molecular weight compounds to increase their solubility and excretion rate; for instance, benzoimidazol, benzothiophen, and benzothiazol are reported as good α-glucosidase inhibitors. 17 Noori et al 18 have reported benzoimidazol with acetamide derivatives as an α-glucosidase inhibitor. Benzothiazine acetamide derivatives are well-known anti-diabetic, 16 anti-inflammatory, 19 anti-leukemic, 20 , 21 anti-microbial, 22 monoamine oxidase (MAO) inhibitors, 23 endothelin receptor antagonists (ERA), 24 antiallergic and antioxidant compounds.…”
Section: Introductionmentioning
confidence: 99%